Multi-analyte profiling and pathway analysis of plasma for proteins associated with cancer-related fatigue syndrome in disease-free breast cancer patients after primary treatment. Issue 4 (7th June 2013) - Minton, O; Coulton, G R; Stone, P
Abstract : Context: A significant number of women treated for breast cancer develop long-term fatigue afterwards. Previous research has suggested that fatigue may be due to a prolonged inflammatory response. However, there are conflicting results and the exact nature of the disturbance remains unclear. Objectives: To identify inflammatory markers associated with fatigue. Methods: We recruited women from a breast cancer follow-up clinic and categorised them on the basis of a diagnostic interview as to whether they met the criteria for cancer-related fatigue syndrome (cases) or not (controls). We took plasma samples from each participant to analyse subsequently using a panel of 88 biological markers. Results: 90 samples were analysed in total (45 cases and 45 controls). A factorial analysis of variance (using age as a fixed factor) demonstrated a number of differences in inflammatory cytokines. There were 28 significantly different analytes in total. Granulocyte colony stimulating factor was the most significantly different analyte (p<0.001). Many of the significant analytes were chemokine ligands found to be linked through an inflammatory pathway promoting T-cell and granulocyte production and activation. Conclusions: Our results add further weight to the hypothesis that cancer-related fatigue syndrome is associated with an increased pro-inflammatory immune response. Our findings indicate that these cytokine changes could underpin the subjective symptoms, such as perceived muscle weakness and concentration difficulties, experienced by women who feel fatigued after treatment.